Smart city multi-source data correlation methods - Ge, Xueqing (SPIE, 2024)
With the acceleration of urban construction and intelligence, the sources of multi-source data in cities have become more extensive, and the data from internal city management platforms has exploded. Multi-source data linkage is a method that enables the fusion of data from different sectors, which can help city managers to interpret comprehensive information about the objects of concern from multiple perspectives, and provide more scientific and accurate guidance for the management and development of the city. Based on the developed data management platform, through data pre-processing, multi-source data integration, matching and analysis, and the calculation of textual similarity of field descriptions of relevant subject data tables, it can effectively assist data management personnel to determine the correlation between data to support the subsequent multi-faceted data query and multi-dimensional information presentation.